DISIPLIN DITINJAU DARI TANGGUNG JAWAB DENGAN HUBUNGAN GURU-SISWA SEBAGAI MEDIATOR PADA SISWA SEKOLAH MENENGAH PERTAMA - , WILDA FASIM HASIBUAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Discipline is an absolute must in the school, without the discipline of teaching and learning would not run properly. Awareness of being disciplined influenced by many factors, one of which is responsibility. Responsibilities would lead students to always be able to control his behavior. However, discipline and responsibility would not just show up in students, to foster both required teacher-student relationship that exists either, so from this connection that students could internalize the discipline and responsibility on himself. The purpose of this research was the responsibility of the teacher-student relationship as a mediator influence Islamic âXâ Secondary School student discipline. This study involved 110 subjects Islamic 'X' secondary students in Yogyakarta, data retrieval using a scale of discipline, responsibility, and the teacher-student relationship. Analysis of the data used was regression analysis Baron and Kenny.The results of this study revealed no significant effect of responsibility for discipline with p = 0.414 (p <0.05). Data on the first calculation to determine whether further calculations would be continued. From the above data obtained further calculations couldnot be done, in other words the mediation regression analysis could not be performed and the hypothesis is rejected.